Effectiveness of Epidural Analgesia, Continuous Surgical Site Analgesia, and Patient-Controlled Analgesic Morphine for Postoperative Pain Management and Hyperalgesia, Rehabilitation, and Health-Related Quality of Life After Open Nephrectomy: A Prospective, Randomized, Controlled Study. (January 2017) - Capdevila, Xavier; Moulard, Sebastien; Plasse, Christian; Peshaud, Jean-Luc; Molinari, Nicolas; Dadure, Christophe; Bringuier, Sophie
Abstract : BACKGROUND: There is no widely recognized effective technique to optimally reduce pain scores and prevent persistent postoperative pain after nephrectomy. We compared continuous surgical site analgesia (CSSA), epidural analgesia (EA), and a control group (patient-controlled analgesic morphine) in patients undergoing open nephrectomy. METHODS: Sixty consecutive patients were randomized to be part of EA, CSSA, or control groups postoperatively for 72 hours. All patients received patient-controlled analgesic morphine, if needed. Hyperalgesia was assessed on the first, second, and third postoperative days. Chronic pain characteristics and quality of life were analyzed at 1 and 3 months. The primary outcome was the pain score at 24 hours. Secondary outcomes were morphine consumption, postoperative rehabilitation, hyperalgesia, chronic pain incidence, and quality-of-life parameters. RESULTS: At 24 hours, mean ± standard deviation pain values at rest (2.4 ± 1.7, 2.2 ± 1.2, and 4.2 ± 1.2, respectively, in EA, CSSA, and control groups, P <.001) and during coughing was lower in the EA and CSSA groups. Total morphine consumption was higher in the control group. Rehabilitation parameters improved sooner in the EA and CSSA groups. Median values of area of hyperalgesia differed at 48 hours between the EA group and the control group (36.4 cm 2 ) and (52 cm 2 ) ( P = .01) and at 72 hours among the EA group, CSSA group, and the control group (40 cm 2, 39.5 cm 2, and 59 cm 2, respectively; P = .002). CSSA reduced the severity of pain and hyperalgesia at 1 month and optimized quality of life 3 months after surgery (role physical scores, P = .005). CONCLUSIONS: CSSA and EA significantly improve postoperative analgesia, reduce postoperative morphine consumption, area of wound hyperalgesia, and accelerate patient rehabilitation after open nephrectomy. CSSA significantly reduces the severity of residual pain 1 month after surgery and optimizes quality-of-life parameters 3 months after surgery. Abstract : Supplemental Digital Content is available in the text.